Antioxidant and Antiradical Activity of Coffee - Alexander Yashin; Yakov Yashin; Jing Yuan Wang; Boris Nemzer (MDPI AG, 2013)
This review summarizes published information concerning the determination of antioxidant activity (AA) in coffee samples by various methods (ORAC, FRAP, TRAP, TEAC, etc.) in vitro and limited data of antiradical activity of coffee products in vitro and in vivo. Comparison is carried out of the AA of coffee Arabica and coffee Robusta roasted at different temperatures as well as by different roasting methods (microwave, convection, etc.). Data on the antiradical activity of coffee is provided. The antioxidant activity of coffee, tea, cocoa, and red wine is compared. At the end of this review, the total antioxidant content (TAC) of coffee samples from 21 coffee-producing countries as measured by an amperometric method is provided. The TAC of green and roasted coffee beans is also compared.